Trichophoromyia iorlandobaratai (Diptera: Psychodidae), a new phlebotomine species from the Brazilian Amazonia - Santos, Thiago Vasconcelos dos (Oxford University Press, 2019)
Trichophoromyia iorlandobaratai sp. n. Vasconcelos dos Santos, Santos Neto, S?nchez Uzc?tegui & Galardo is described and illustrated on the basis of male specimens collected in the municipality of Itaituba, Par? State, Brazilian Amazonia. This species can be differentiated from other morphologically similar species within Trichophoromyia by means of the male characters such as the ratio between the aedeagal ducts/sperm pump, shape and distribution of setae in the gonocoxite, and particularly the distinct shape of paramere.